Silencing the alarm: an insect salivary enzyme closes plant stomata and inhibits volatile release. Issue 2 (16th February 2021) - Lin, Po‐An; Chen, Yintong; Chaverra‐Rodriguez, Duverney; Heu, Chan Chin; Zainuddin, Nursyafiqi Bin; Sidhu, Jagdeep Singh; Peiffer, Michelle; Tan, Ching‐Wen; Helms, Anjel; Kim, Donghun; Ali, Jared; Rasgon, Jason L.; et al.
Summary: Herbivore‐induced plant volatiles (HIPVs) are widely recognized as an ecologically important defensive response of plants against herbivory. Although the induction of this 'cry for help' has been well documented, only a few studies have investigated the inhibition of HIPVs by herbivores and little is known about whether herbivores have evolved mechanisms to inhibit the release of HIPVs. To examine the role of herbivore effectors in modulating HIPVs and stomatal dynamics, we conducted series of experiments combining pharmacological, surgical, genetic (CRISPR‐Cas9) and chemical (GC‐MS analysis) approaches. We show that the salivary enzyme, glucose oxidase (GOX), secreted by the caterpillar Helicoverpa zea on leaves, causes stomatal closure in tomato ( Solanum lycopersicum ) within 5 min, and in both tomato and soybean ( Glycine max ) for at least 48 h. GOX also inhibits the emission of several HIPVs during feeding by H. zea, including ( Z )‐3‐hexenol, ( Z )‐jasmone and ( Z )‐3‐hexenyl acetate, which are important airborne signals in plant defenses. Our findings highlight a potential adaptive strategy where an insect herbivore inhibits plant airborne defenses during feeding by exploiting the association between stomatal dynamics and HIPV emission.